Sejarah Pelestarian dan Penyebaran Informasi: Menuju Masyarakat Informasi - Hasanah, Nuning; Suharto, Toto (Jurnal Tadwin, 2023)
The article aims to describe the information from a historical perspective. Knowledge of the history of information becomes important, considering that society is dynamic, transforms and shifts from an agricultural based-society to an industrial based, and recent becomes the information society today. Documentation technique used to collect data related to information preservation and information dissemination historically. This article uses historical analysis to explain the development of information, especially in its preservation and dissemination. This article found that the preservation of information has taken a long time, i.e. ever since humans as "being of thought" began to recognize how to write and read. The information is preserved in script form in the earliest form and then developed into print form. The information is disseminated through various media and types, ranging from manual to digital. Based on these findings, multiple forms of preservation and dissemination of information are constantly developing to create a society that puts information as wisdom in life.